(untitled) - Clouse, Barbara Fine (New York, 2005)
This troubleshooting guide covers all aspects of writing for beginning nonfiction writers. It pinpoints the challenges writers can encounter at every stage of the writing process--from prewriting and drafting to revising and editing --and provides effective procedures and problem-solving strategies for overcoming them.
Keywords: English language,English language,Report writing; Rhetoric,Grammar